2019
DOI: 10.17559/tv-20190819080524
|View full text |Cite
|
Sign up to set email alerts
|

Salt Freeze-Thaw Damage Characteristics of Concrete based on Computed Tomography

Abstract: Freeze-thaw damage and salt erosion are important factors that influence the durability of concrete. In this study, degradation laws of concrete in salt freezethaw environment were discussed from the microscopic perspective based on the 3D reconstruction of computed tomography images. A damage model based on concrete aggregate volume and porosity was constructed. Furthermore, the main causes of concrete degradation in the salt freeze-thaw environment were analyzed. Results reveal that, with the increase in sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…To confirm the proportion of coarse aggregate in a concrete structure, it is necessary to obtain an image of the internal structure of the concrete. Computed tomography (CT), as a non-destructive testing method, is widely used to explore the internal structure of concrete and its development [28][29][30][31]. It can clearly, accurately and intuitively display the internal structure, composition, material and defect status of the detected object in the form of two-dimensional tomographic images or three-dimensional images under the condition of no damage to the detected object [32][33][34], and it is known as the best nondestructive testing and non-destructive assessment technology today.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the proportion of coarse aggregate in a concrete structure, it is necessary to obtain an image of the internal structure of the concrete. Computed tomography (CT), as a non-destructive testing method, is widely used to explore the internal structure of concrete and its development [28][29][30][31]. It can clearly, accurately and intuitively display the internal structure, composition, material and defect status of the detected object in the form of two-dimensional tomographic images or three-dimensional images under the condition of no damage to the detected object [32][33][34], and it is known as the best nondestructive testing and non-destructive assessment technology today.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [20] showed that the presence of biomass ash does not appear to have a significant impact on the freezing and thawing behaviour with a proper amount of air entraining agent. Addition of chemical admixture for air entraining in concrete air can also increase freeze/thaw resistance with de-icing salt of concrete [22]. The effect of wood ash on the drying shrinkage of cement composites depends on the level of replacement of cement.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on concrete damaged by salt freeze mainly focus on durability life predictions of concrete and mechanical performance and the influence of different mineral contents on concrete frost resistance [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] to investigate the change in concrete properties after salt and frost damage. Some researchers have used CT scanning technology to show the micro-structure of the concrete [ 33 , 34 , 35 , 36 , 37 , 38 ]. They discussed the application prospect of CT scanning technology in the concrete pore and two-dimensional (2D) scanning section.…”
Section: Introductionmentioning
confidence: 99%